True intrusion of maxillary first molars with zygomatic and palatal miniscrew anchorage: a case report - Tripathi Tulika; Kalra Shilpa; Rai Priyank; Faraz Farrukh; Singh Navneet (Sciendo, 2016)
The intrusion of the maxillary first molar is indicated when occlusal clearance is needed for prosthetic rehabilitation. Maxillary molar intrusion may be undertaken using skeletal anchorage systems to avoid complicated mechanics delivered by conventional intra-oral fixed appliances. In the present case report, the efficient use of orthodontic miniscrew anchorage by applying simple mechanics for true maxillary first molar intrusion is described. This was followed by the rehabilitation of the mandibular first molar spaces with implant prostheses. A 16-year-old female patient had masticatory difficulty due to the bilateral overeruption of the maxillary first molars and carious mandibular first molars. True intrusion of each maxillary first molar was achieved using zygomatic and palatal paramedian miniscrews placed in line with the central axis of the teeth. Simultaneously, alignment of the upper arch was achieved via fixed appliance therapy. Using two orthodontic miniscrews to intrude each maxillary molar, orthodontic treatment was simplified by eliminating the need for miniplate placement by extensive surgery and the creation of intra-oral multiunit anchorage. Masticatory efficiency was improved by increasing the occlusal table with prosthetic rehabilitation of the mandibular first molar spaces with dental implant prostheses.